Gender and Personality Drivers of Consumer Mixed Emotional Responses to Advertising - Orth,Ulrich; Malkewitz,Keven; Bee,Colleen (Journal of Current Issues and Research in Advertising, 2010)
This research sheds insight on how consumer gender and personality produce different levels of mixed emotions in response to advertising resulting in divergent brand attitudes. Using a more complete measure of emotional response than previously used in advertising research, we manipulate the perceived incongruity between advertisement role portrayals and viewers’ self concept and show that women exhibit higher levels of mixed emotions than do men, but they respond with more favorable attitudes toward the advertised brand. Further, individuals who are more neurotic, introvert, or antagonistic experience higher levels of mixed emotions, and respond with less favorable attitudes when experiencing ad-evoked mixed emotions. Implications focus on advancing mixed emotions, gender, and personality research, and on the use of sex role portrayals in advertising.
Keywords: Marketing; MBA